Taking the fifth amendment in Turing's imitation game. Issue 2 (4th March 2017) - Warwick, Kevin; Shah, Huma
Abstract: In this paper, we look at a specific issue with practical Turing tests, namely the right of the machine to remain silent during interrogation. In particular, we consider the possibility of a machine passing the Turing test simply by not saying anything. We include a number of transcripts from practical Turing tests in which silence has actually occurred on the part of a hidden entity. Each of the transcripts considered here resulted in a judge being unable to make the 'right identification', i.e., they could not say for certain which hidden entity was the machine.